The Implementation Process of Two Evidence-Based Protocols: A Spatial Neglect Network Initiative - Hreha, Kimberly; Barrett, A. M.; Gillen, Robert W.; Gonzalez-Snyder, Chris; Masmela, Jenny; Chen, Peii (Frontiers in Health Services, 2022)
Introduction Spatial neglect, a neurocognitive disorder of lateralized spatial attention, is prevalent among stroke survivors especially in inpatient rehabilitation facilities (IRFs). The ultimate goal of the project was to improve spatial neglect care in inpatient rehabilitation and trained as many OTs as possible using both tools in their regular practices as the means to achieve our overall objective. Therefore, we conducted a project aimed at implementing two evidence-based protocols, one for assessment (KF-NAP®) and the other for treatment (KF-PAT®), and share the implementation process, which included barriers and facilitators identified during and after the process, and implementation outcomes. Methods Sixteen IRFs were involved. The Knowledge-To-Action Cycle was used to describe the process of knowledge inquiry (training), translating knowledge (implementation) and evaluating the use of knowledge in clinical practice (outcomes). Barriers and strategies were reported using the Consolidated Framework for Implementation Research and identified through a survey, after the study concluded. Results Thirty-two therapists at the participating sites were trained to some level of the KF-NAP and KF-PAT. Throughout the project and also once after it finished, different barriers were identified by researchers and clinicians, who then determined together actions to eliminate or minimize the barriers. For example, multiple sites reported: “not having time to train other staff at their hospital due to high patient volume and other responsibilities.” Discussion The project shared our implementation process which demonstrated the importance of using implementation methods and incorporating a researcher-clinician partnership, not only for knowledge generation but also knowledge translation. Frequent communications and exchanging information with stakeholders at different levels, may be determinant to the success of each implementation phase. Further research is needed.